"الأحاديث الواردة في سنية القبض في الصلاة" "جمعا ودراسة" - شو ا رب, عبد الرؤوف (University of Eloued-جامعة الوادي, 2016)
الحمد لله رب العامين والصلاة والسلام على أشرف المرسلين محمد وعلى آلو وصحبو أجمعين وأشهد أن محمدا عبده ورسولو وبعد: إن ىذا البحث لو تعلق بأمر يعد من أىم أركان الدين، ألا وىي الصلاة، ولهذا الركن صفات نقلت عنو صلى الله عليو وسلم في كيفية أدائها على الصفة الصحيحة، ومن بينها قبض اليدين في الصلاة، جاءت في ذلك أحاديث صحيحة رويت في كتب السنة كالموطأ، والصحيحين، وقد قسمت بحثي إلى فصلين، الفصل الأول، ويتعلق بالأحاديث، والآثار التي تثبت سنية ىذه الصفة، وبيان محل وضع اليدين في الصلاة، والفصل الثاني، ويشتمل على صفة وضع اليدين، والمؤلفات التي عنيت بهذه المسألة، والمبحث الثاني، وفيو القائلين بخلاف ىذه الصفة، من أىل السنة من ) رواية ابن القاسم، والآثار الضعيفة(، ومن غير أىل السنة، الإباضية، والشيعة، مع بيان وجو الصواب، والله أسأل أن يهدينا لما اختلف فيو من الحPraise be to Allah, the Lord of years , prayer and peace be upon His Messengers Muhammad and his family and companions and I bear witness that Muhammad is His :slave and His Messenger, and after This research has suspended the order is one of the most important pillars of Islam , namely to pray, but this corner recipes quoted him as God's peace be upon him how to perform the correct character , including catch your hands in prayer, came the talk properly recounted in the books of the year Kalmuto , and correct , our research has divided into two chapters , the first chapter , and the respect with talk , and effectsProve a Sunni as such , the statement replaces Put your hands in prayer, and the seconD chapter , and includes a recipe hands mode, and compositions that are meant to this issue , and the second section , in which those who say other than this quality , it is the Sunnis ( narrated by Ibn al-Qasim , the weak and the effects) , and non- Sunnis , Ibadi , and Shiites , with the face of the statement is correct, and I ask God to guide .us to the truth, with his permission that he is able todo it
مذكرة